Impact of Intrauterine Growth Restriction on the Capillarization of the Early Postnatal Rat Heart. Issue 9 (7th January 2019) - Sutherland, Megan R.; Ng, Ka Wing; Drenckhahn, Jörg D.; Wlodek, Mary E.; Black, Mary Jane
ABSTRACT: Capillarization plays a key role in the growth of the developing heart. We therefore hypothesized that impaired heart development following intrauterine growth restriction (IUGR) may arise from inadequate myocardial capillary growth. The aims of the study were to examine the effect of IUGR on the growth and diffusion radius of intramyocardial capillaries in rats at postnatal day 1. Uteroplacental insufficiency was induced in rats in late gestation (E18, term = E22) by bilateral uterine artery and vein ligation (restricted offspring N = 12; six males and six females); offspring from sham‐operated dams were used as controls (N = 10; five males and five females). At postnatal day 1, the hearts were immersion‐fixed and heart volume, capillary length density, capillary diffusion radius, and total capillary length were stereologically determined. Restricted offspring were significantly smaller at birth, with a concomitant reduction in heart volume and total myocardial capillary length compared to controls. Capillary growth was not impaired relative to heart size, with no significant differences in capillary length density or diffusion radius in the myocardium of restricted and control offspring. There were no sex differences in any of the parameters examined. In conclusion, there was no evidence to indicate that microvascular development is compromised in the heart of IUGR offspring at 1 day after birth. Total myocardial capillary length, however, was significantly reduced in the growth restricted offspring and further longitudinal studies are required to elucidate the long‐term impact, particularly following hypertrophic cardiac growth. Anat Rec, 302:1580–1586, 2019. © 2018 American Association for Anatomy